A grouping strategy for the multi-group full-spectrum K-distribution method in gas mixtures. (October 2019) - Liu, Guanghai; Liu, Yuying; Liu, Fengshan; Consalvi, Jean-louis
Highlights: A new grouping strategy for MGFSK in gas mixtures is proposed. The grouping strategy can extend the application scope from single radiating species to mixtures. MGFSK outperforms both FSCK and RC-FSK in the two-layer systems. Both RC-FSK and MGFSK perform better than FSCK in oxy-fuel flames. Abstract: The Multi-Group Full-Spectrum K-distribution method (MGFSK) is a promising method for efficient and accurate thermal radiation calculations in participating media with strong temperature inhomogeneity. The current MGFSK method cannot be used for modeling radiative transfer in gas mixtures since it is applicable only to a single radiating gas. To make MGFSK applicable to mixtures without losing efficiency, a new grouping strategy for gas mixtures is proposed based on a scaling function of the mixture. Several one-dimensional two-layer systems with large temperature gradient and a two-dimensional oxy-fuel flame are simulated to demonstrate the accuracy of the modified MGFSK method (MGFSK-M). The simulation results are compared with those of the Line-by-Line model, the Full-Spectrum Correlated K-distribution method (FSCK) and the Rank Correlated Full-Spectrum K-distribution method (RC-FSK). MGFSK-M significantly outperforms both FSCK and RC-FSK in the two-layer systems. For the oxy-fuel flame, RC-FSK and MGFSK-M offer similar accuracy and both perform better than FSCK.